Os sentidos da escolarização para mulheres no rural de Feira de Santana/Bahia: narrativas de trajetórias e sonhos de mulheres da Eja - Araújo, Vanda Almeida da Cunha (2014)
This thesis presents a study of life histories and school experiences of adult women of the rural district of Maria Quiteria in Feira de Santana/BA. The study sought to understand the meanings of schooling for women who return to the school in the course of Education for Young People and Adults, to complete the elementary education of the headquarters of his rural district. The work examines issues related to place of residence (rural areas), deals with gender relations and reflects the conditions of life and work of women surveyed. The education for the people in the field was historically relegated the educational proposals without specificities and originality territorial, facing many times the programs and projects of rapid duration without due attention to the contexts in which they were part. These proposals have not promoted structural changes for the improvement of the quality of life of the people in the field and as a consequence, the banished from school and encouraged them to seek other conditions of life, work and study in the large urban centers. Using a qualitative approach, the methodology of this study, develop ping from their life stories, trying to understand the reality in focus, whereas the representations, the identities constructed and knowledge stemming from the trajectory experienced by women students of Young Adults Education in night shift. The research relied on the collaboration of six women living in surrounding communities of the district, students of the school. The instruments used for data collection were the observation in school, in the communities and households; the comments participants in the classroom, the questionnaires for the characterization of the general profile of the students and the semi-structured interviews with six students. The research reveals the great importance that women attribute to the process of schooling, because for them the conclusion of their studies can provide better employment opportunities, increased self-esteem, respect, appreciation and social recognition. The study also shows that, in the perspective of women, the conclusion of studies allows a better performance in relations developed in the community and society, thus allowing for the same, an effective exercise of citizenship.